Activity Based Learning in Management Education - Kundu, Punam; Dhankhar, Dinesh; Dhunna, Neelam (Gyan Management Journal, 2013)
The concept of management consists of a wide range of interdisciplinary branches including Accountancy, Management, E-Management, Finance, Economics and Marketing. While pursuing a course in the field of management, one thus acquires the knowledge of business or trade, nature and fluctuations in market, basics of economics, fiscal policies, industrial policies etc. And since the Indian economy is one of the fastest growing economies among the third world countries, the need for talented professionals, who can contribute towards the growth of th·e economy, is increasing, these days Management education has emerged as one of the most potential pursuits in the wake of industrialization and has been primarily meant for providing the students in-depth knowledge of different functional areas of business so as to prepare people required by the community for the purposes of trade, management and industry.